Jag-reformen: Olof Lagercrantz på Dagens Nyheters ledarsida 1960–1975 - Otterberg, Stina (Tidskrift för litteraturvetenskap, 2009)
Installing the »I«. Editorials by Olof Lagercrantz in Dagens Nyheter 1960–1975 This study concerns the Swedish writer and critic Olof Lagercrantz who served as both editor in chief and cultural editor of Sweden’s major daily newspaper, Dagens Nyheter, between 1960 and 1975. The material upon which the article is based is a corpus of 300 editorials, mostly unsigned and hitherto unnoticed by scholars. By focusing on matters of style, it is shown that the texts by Lagercrantz distinctively break the laws of the editorial as traditional genre, which in short involved framing in the newspaper’s political standpoints in by speaking from the position of an editorial »we«. Lagercrantz’s editorials differ from this well-trodden mode by using styles of writing that resemble of everyday language and by using forms of letter-writing. To a wide extent, the editorials also play with intertextual allusions to the established literary canon, and often take literature and literary issues as their starting point. The article stresses how Lagercrantz finds strategies of installing »himself« in the text, i.e. how he constantly seeks ways of establishing an »I« in a type of text where this particular word is not allowed. The letter-forms seem to convey the sense of presence of a subject in the text. Metaphors of body and voice, and mentioning of everyday, mundane events create effects of intimacy. Attention is drawn to the fact that Lagercrantz even on the level of grammar conveys a sense of body in the text: the number of substantives is by comparison quite high with Lagercrantz – constantly avoiding the adjective, he prefers words which literally have matter, substance. Finally, it is suggested that the installation of the »I« in the editorials be considered a performance in both a linguistic and theatrical sense. By means of contrast, Lagercrantz’s figurative and literary writing make apparent the laws of the editorial as generally written and understood. The latter thereby also seems to be highlighted as text, as form of language.